2019
DOI: 10.1002/pchj.300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long‐term institutionalization on experiential pleasure and motivation in patients with schizophrenia

Abstract: Anhedonia and amotivation, the hallmarks of negative symptoms in schizophrenia, are believed to be due to “emotion–behavior decoupling,” a failure in translating pleasure experience into appropriate goal‐directed behavior. A number of studies have reported that long‐term institutionalized schizophrenia patients suffer from more severe negative symptoms than community‐dwelling patients, but few studies have investigated pleasure experience and motivational behavior in schizophrenia patients who have experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Regarding the setting of recruitment, older adults admitted to LTI are often socially isolated, have more depressive symptoms, a high prevalence of disability and multimorbidity, and increased cognitive decline (129)(130)(131). In the course of time, institutionalization can make things worse by contributing with the exacerbating of preexisting conditions and with the development of new ones (132)(133)(134)(135). Hence, it is possible that different results might be found in pre-frail and frail community-dwellers.…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding the setting of recruitment, older adults admitted to LTI are often socially isolated, have more depressive symptoms, a high prevalence of disability and multimorbidity, and increased cognitive decline (129)(130)(131). In the course of time, institutionalization can make things worse by contributing with the exacerbating of preexisting conditions and with the development of new ones (132)(133)(134)(135). Hence, it is possible that different results might be found in pre-frail and frail community-dwellers.…”
Section: Limitationsmentioning
confidence: 99%
“…However, the suggestion of a preferential impairment in representational/anticipatory response in schizophrenia has been challenged by more recent studies. Lui et al, (2016a) and Xie et al (2017) both reported a preferential decoupling in evoked/consummatory response, while Chu et al (2020) observed comparable impairment in both types of response. In addition, Heerey and Gold's (2007) finding concerning inappropriate responding to neutral stimuli by subjects with schizophrenia also appears far from robust.…”
Section: General Scientific Summarymentioning
confidence: 86%
“…Second, schizophrenia subjects exhibited excessive inappropriate responses to neutral stimuli (their Figure 3). The first finding has been replicated in people with acute as well as chronic schizophrenia (Lui et al, 2016a;Xie et al, 2017;Chu et al, 2020;Wang et al, 2020), and is widely taken as evidence for a decoupling of behaviour from emotional incentive. However, the suggestion of a preferential impairment in representational/anticipatory response in schizophrenia has been challenged by more recent studies.…”
Section: General Scientific Summarymentioning
confidence: 93%
See 2 more Smart Citations